Coaching diversity in Bulgarian youth football: A factorial, cluster, and SWOT analysis of methodologies and development strategies - Ivanov, Danail (Universitas Tanjungpura, 2025)
Background. Contemporary youth football development requires evidence-based coaching methodologies that align with both theoretical models and practical demands. However, discrepancies between elite and grassroots coaching approaches remain underexplored. This study aimed to identify prevailing pedagogical profiles among Bulgarian youth football coaches and to analyze the systemic factors shaping coaching practice. Methods. A mixed-methods design was employed, combining exploratory factor analysis (EFA), cluster analysis, and SWOT (strengths